The Utility of MMPI–2–RF Scale Scores in the Differential Diagnosis of Schizophrenia and Major Depressive Disorder. Issue 3 (4th May 2018) - Lee, Tayla T. C.; Graham, John R.; Arbisi, Paul A.
ABSTRACT: This study was designed to determine whether scores on selected Minnesota Multiphasic Personality Inventory–2–Restructured Form (MMPI–2–RF) scales could be used to differentiate between individuals diagnosed with schizophrenia (SCZ) and major depressive disorder (MDD). The sample was drawn from 2 psychiatric inpatient hospitals and included data from 199 individuals with SCZ and 808 individuals with MDD. A series of multivariate analyses of variance, analyses of variance, and odds ratios were calculated to determine which MMPI–2–RF scales provide the best differentiation between individuals presenting with these 2 disorders. Results indicated scales assessing internalizing dysfunction, including Emotional/Internalizing Dysfunction (EID), Restructured Clinical Scales Demoralization (RCd), Low Positive Emotions (RC2), Suicidal/Death Ideation (SUI), and Self Doubt (SFD) best discriminated MDD from SCZ. Scales assessing thought dysfunction, incluidng Thought Dysfunction (THD), Restructured Clinical Scales Ideas of Persecution (RC6) and Aberrant Experiences (RC8), and Psychoticism-Revised (PSYC-r) were demonstrated to best identify SCZ. Comparisons of the examined MMPI–2–RF scales to MMPI–2 scales assessing similar constructs suggested scales from the MMPI–2–RF perform similarly to their MMPI–2 counterparts in detecting MDD or SCZ, but might have increased ability to discriminate SCZ from other conditions. Overall, results of this study suggest that scores on the examined MMPI–2–RF scales provide important information about the differential diagnosis of MDD and SCZ to clinicians working in inpatient settings.